Exploring social media and admissions decision-making – friends or foes? - Law, Marcus; Mylopoulos, Maria; Veinot, Paula; Miller, Daniel; Hanson, Mark (Canadian Medical Education Journal, 2016)
Background: Despite the ever-increasing use of social media (e.g., Facebook, Twitter) little is known about its use in medical school admissions. This qualitative study explores whether and how social media (SM) is used in undergraduate admissions in Canada, and the attitudes of admissions personnel towards such use. Methods: Phone interviews were conducted with admissions deans and nominated admissions personnel. A qualitative descriptive analysis was performed using iterative coding and comparing, and grouping data into themes. Results: Personnel from 15 of 17 Canadian medical schools participated. A sizeable proportion had, at some point, examined social media (SM) profiles to acquire information on applicants. Participants did not report using it explicitly to screen all applicants (primary use); however, several did admit to looking at SM to follow up on preliminary indications of misbehaviour (secondary use). Participants articulated concerns, such as validity and equity, about using SM in admissions. Despite no schools having existing policy, participants expressed openness to future use. Conclusions: While some of the 15 schools had used SM to acquire information on applicants, criteria for formulating judgments were obscure, and participants expressed significant apprehension, based on concerns for fairness and validity. Findings suggest participant ambivalence and ongoing risks associated with “hidden” selection practices.